Existence of the Literacy Community "Gerakan Musi Membaca" and Children's Reading Interest in Musibanyuasin - Ahmad Suradi; Nilawati Nilawati; Abdullah Idi (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
This study aims to reveal the existence of the literacy community "Gerakan Musi Membaca" and the implications of its existence in the development of children's reading interest in Musi Banyuasin. This research is a qualitative study, the primary source of which comes from literacy actors and school children in Musi Banyuasin. Data collection techniques used were interviews and direct observation in the research field. The results showed that the literacy community of the Musi Reading Movement was a community that moved to increase the reading interest of the surrounding community. To support and attract visitors, the Literacy Movement reading literacy community provides a variety of books. The existence of this literacy community is very helpful to the community in improving reading, by planning the procurement of a book collection in the form of activities to formulate the objectives of the program to be held, determine the techniques to be used, and identify the collection of readings. There are several obstacles in this activity namely the surrounding environment still often looks at odd people who spend time reading for example while waiting in line, or just sitting in a city park while reading.